P119 The association of hand and wrist injuries with other skeletal injuries in multiple trauma patients in a UK Major Trauma Centre. (8th April 2021) - Tsinaslanidis, Prodromos; Smith, Toby O; Brown, Oliver S; Tsinaslanidis, George; Umarji, Shamim; Hing, Caroline B
Abstract: Background: There are 20, 000 major trauma cases in England annually yet the association with concomitant upper limb injuries is unknown. Injuries of the hand and wrist can cause serious functional impairment, decreased quality of life and confer a significant economic burden to healthcare systems. The aim of this study was to determine the incidence, injury pattern and association of hand/wrist injuries with other injuries and the ISS score in multiple trauma patients in the UK. Methods: A single centre retrospective cohort study was performed at a level one trauma centre. Trauma Association & Research Network (TARN) eligible patients during a 5-year period were included. Results: A total of 107 patients were included in this study. Seventy patients had an ISS<15 and 37: had an ISS>15. The majority were male (70.1%) and the mean age was 45 Years. Hand and wrist injuries were the second most common injury found in 26.2% of patients. There was a significant association between hand/wrist injuries and lower limb injuries (p = 0.04) and pelvic injuries (p = 0.02). The association between hand and wrist injuries with ISS score was found to be not significant (p = 0.82). Conclusion: Hand and wrist injuries should be screened for in multiply injured patients with a pelvic or lower limb injury.